ANALYSIS OF THE CHIRPLET TRANSFORM-BASED ALGORITHM FOR RADAR DETECTION OF ACCELERATED TARGETS - Galushko, V. G.; Vavriv, D. M. (Видавничий дім «Академперіодика», 2017)
PACS number: 84.40.Xb Purpose: Efficiency analysis of an optimal algorithm of chirp signal processing based on the chirplet transform as applied to detection of radar targets in uniformly accelerated motion.Design/methodology/approach: Standard methods of the optimal filtration theory are used to investigate the ambiguity function of chirp signals.Findings: An analytical expression has been derived for the ambiguity function of chirp signals that is analyzed with respect to detection of radar targets moving at a constant acceleration. Sidelobe level and characteristic width of the ambiguity function with respect to the coordinates frequency and rate of its change have been estimated. The gain in the signal-to-noise ratio has been assessed that is provided by the algorithm under consideration as compared with application of the standard Fourier transform to detection of chirp signals against a “white” noise background. It is shown that already with a comparatively small (<20) number of processing channels (elementary filters with respect to the frequency change rate) the gain in the signal-tonoise ratio exceeds 10 dB. A block diagram of implementation of the algorithm under consideration is suggested on the basis of a multichannel weighted Fourier transform. Recommendations as for selection of the detection algorithm parameters have been developed.Conclusions: The obtained results testify to efficiency of application of the algorithm under consideration to detection of radar targets moving at a constant acceleration. Nevertheless, it seems expedient to perform computer simulations of its operability with account for the noise impact along with trial measurements in real conditions.Key words: target detection, optimal filtering, chirplet transform, ambiguity function, signal-to-noise ratioManuscript submitted 30.05.2016Radio phys. radio astron. 2017, 22(2): 157-165REFERENCES1. LEVIN, B. R., 1968. Theoretical fundamentals of statistical radio engineering, Volume 2. Moscow, USSR: Sov. radio Publ. (in Russian). 2. FINKELSTEIN, M. I., 1983, Fundamentals of radiolocation. Moscow, USSR: Radio i Svyaz' Publ. (in Russian). 3. SHIRMAN, Y. D. and MANZHOS, V. N., 1981. Theory and technique of processing radar information against a noise background. Moscow, USSR: Radio i Svyaz' Publ. (in Russian). 4. HARMUTH, H. F., 1981. Nonsinusoidal Waves for Radar and Radio Communication. New York: Academic Press. 5. BERNI, A. J. and GREEG, W. D., 1973, On the Utility of Chirp Modulation for Digital Signaling. IEEE Trans. Commun. vol. 21, no. 6, pp. 748–751. DOI: https://doi.org/10.1109/TCOM.1973.1091721 6. MENG FANYU and GU XUEMAI, 2011. A Combined Chirp Signal Modulation Technique for Multiple Access Systems. Inform. Technol. J. vol. 10, no. 2, pp. 416–421. DOI:https://doi.org/10.3923/itj.2011.416.421 7. PODLESNY, A. V., BRYNKO, I. G., KURKIN, V. I., BEREZOVSKY, V. A., KISELYEV, A. M., and PETUT,KHOV, E. V., 2013. A multifunctional chirp ionosonde for monitoring of the ionosphere Heliogeophys. Res. [online]. is. 4, pp. 24–31 [viewed 16 May 2017] (in Russian). Available from: http://vestnik.geospace.ru 8. SUKHANOV, D. YA. and YAKUBOV, V. P., 2010. Application of linear frequency modulated signals in threedimensional radio tomography. Tech. Phys. vol. 55, is. 4, pp. 546–550. DOI: http://10.1134/1063784210040195 9. COOK, C. E. and BERNFELD, M., 1967. Radar Signals: An Introduction to Theory and Application. New York - London: Academic Press. 10. TUTYGIN, V. S., SHEDOV, S. V. and YUZHAKOV, A. V., 2011. New adaptive algorithms for detection and parameter estimation of chirp signals. Digital signal rpocessing. no. 1, pp. 16–23 (in Russian). 11. MANN, S. and HAYKIN, S., 1991. The Chirplet transform: A generalization of Gabor's logon transform. In: Vision Interface 91 International Conference Proceedings. Calgary, Alberta, Canada, pp. 205–212. 12. ABRAMOWITZ, M. and STEGUN, I. A., eds. 1964. Handbook of mathematical functions with formulas, graphs and mathematical tables. U. S. Department of Commerce, National Bureau of Standards.